Training for Labour’s Professionals - Nesbit, Tom (Just Labour, 2002)
This article addresses an issue arising from a comparative study of the nature of education and training for Canadian full-time union staff and officials. The specific question is how can education for union officials address both the social and the servicing demands placed on them? The article locates the discussion about such training within the contexts of existing approaches to labour education and current debates about the revitalization of the labour movement. It concludes with a call for more systematic discussion of these issues and further analysis of different programmatic training models. Cet article porte sur une question découlant d’une étude comparative de la nature de l’éducation et de la formation données aux dirigeants et dirigeantes et membres du personnel à plein temps des syndicats au Canada. La question est celle de savoir comment l’on peut voir à ce que la formation donnée à ces « cadres » syndicaux leur permette de répondre aux exigences sociales et de prestation de services qui leur sont imposées. L’article place cette formation dans le contexte des approches actuelles d’éducation syndicale et du débat au sujet de la revitalisation du mouvement syndical. Il se termine par un appel à un examen plus méthodique de ces questions et à une analyse plus poussée de différents modèles de programmes de formation.